Intravenous Lidocaine Does Not Improve Neurologic Outcomes after Cardiac Surgery: A Randomized Controlled Trial. (June 2019) - Klinger, Rebecca Y.; Cooter, Mary; Bisanar, Tiffany; Terrando, Niccolò; Berger, Miles; Podgoreanu, Mihai V.; Stafford-Smith, Mark; Newman, Mark F.; Mathew, Joseph P.; Blumenthal, James A.; Karhausen, Jorn A.; Kertai, Miklos D.; et al.
Editor's Perspective: What We Already Know about This Topic: Preclinical and clinical studies suggest that lidocaine might be neuroprotective, which could benefit surgical patients at risk of neurologic compromise What This Article Tells Us That Is New: This multicenter trial of intravenous lidocaine administered during and after cardiac surgery did not show an effect on cognition at 6 weeks postoperatively Background: Cognitive decline after cardiac surgery occurs frequently and persists in a significant proportion of patients. Preclinical studies and human trials suggest that intravenous lidocaine may confer protection in the setting of neurologic injury. It was hypothesized that lidocaine administration would reduce cognitive decline after cardiac surgery compared to placebo. Methods: After institutional review board approval, 478 patients undergoing cardiac surgery were enrolled into this multicenter, prospective, randomized, double-blinded, placebo-controlled, parallel group trial. Subjects were randomized to lidocaine 1 mg/kg bolus after the induction of anesthesia followed by a continuous infusion (48 μg · kg −1 · min −1 for the first hour, 24 μg · kg −1 · min −1 for the second hour, and 10 μg · kg −1 · min −1 for the next 46 h) or saline with identical volume and rate changes to preserve blinding. Cognitive function was assessed preoperatively and at 6 weeks and 1 yr postoperatively using a standard neurocognitive test battery. The primary outcome was change in cognitive function between baseline and 6 weeks postoperatively, adjusting for age, years of education, baseline cognition, race, and procedure type. Results: Among the 420 allocated subjects who returned for 6-week follow-up (lidocaine: N = 211; placebo: N = 209), there was no difference in the continuous cognitive score change (adjusted mean difference [95% CI], 0.02 (−0.05, 0.08); P = 0.626). Cognitive deficit (greater than 1 SD decline in at least one cognitive domain) at 6 weeks occurred in 41% (87 of 211) in the lidocaine group versus 40% (83 of 209) in the placebo group (adjusted odds ratio [95% CI], 0.94 [0.63, 1.41]; P = 0.766). There were no differences in any quality of life outcomes between treatment groups. At the 1-yr follow-up, there continued to be no difference in cognitive score change, cognitive deficit, or quality of life. Conclusions: Intravenous lidocaine administered during and after cardiac surgery did not reduce postoperative cognitive decline at 6 weeks. Abstract : This multicenter trial of intravenous lidocaine administered during and after cardiac surgery did not show an effect on cognition at 6 weeks postoperatively.Supplemental Digital Content is available in the text.